PENGEMBANGAN POTENSI WISATA DESA KANDANGMAS MELALUI FGD (FOCUS GROUP DISCUSSION) DAN PRA (PARTICIPATORY RURAL APPRAISAL) - Anisa Handayani; Viq Robi Ahmad Wardani; Tegar Susilo Nugroho; Hima Naili Hidayah; Mohammad Khasan (LPPM Institut Pendidikan Nusantara Global, 2025)
Kandangmas Village, located in Dawe District, Kudus Regency, has tourism potential that positively impacts community activities. One of the tourism potentials is the artificial tourism at Logung Dam, but Logung Dam tourism has many obstacles, one of which is the lack of visitors. Therefore, intervention is needed for the community using the FGD (Focus Group Discussion) and PRA (Participatory Rural Appraisal) methods. This development activity was carried out by the PPK Ormawa Team of the BEM Faculty of Psychology, Muria Kudus University, for the 2024 period, consisting of thirteen members, four volunteers, and one supervising lecturer. The target groups for this development activity are POKDARWIS (Tourism Awareness Groups), BUMDes (Village-Owned Enterprises), and Karang Taruna (Youth Organization). Based on the implementation of the development, the FGD and PRA methods are very effective for developing tourism potential, as they can involve and reactivate less active target groups and produce the output of a tourism potential map in Kandangmas Village, which is categorized into several tourism potentials: religious tourism, natural tourism, Logung Dam tourism, art and cultural tourism, culinary tourism, handicraft tourism, and integrated tourism with existing tourist attractions around Kandangmas Village.